Philip W. Bonsal papers - Bonsal, Philip W. (Philip Wilson), 1903-1995.; Ollivier, Emile, 1825-1913.
Correspondence, diaries, memoranda, speeches, and statesments documenting Bonsal's foreign service career, especially as U.S. ambassador to Cuba during and after the 1959 revolution there. Includes material on the differences between Cordell Hull and Sumner Welles regarding Argentina and ideological battles at international meetings over the independence of colonial Africa. Also includes Bonsal's English translation from the French of Emile Ollivier's book L'Expedition du Mexique (1914) concerning Maximilian, Emperor of Mexico.
Diplomat.
Collection material in English, with French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hull, Cordell, -- 1871-1955.; Maximilian, -- Emperor of Mexico, -- 1832-1867.; Welles, Sumner, -- 1892-1961.; International agencies; Colonies -- Africa; Africa -- Politics and government -- 20th century; Argentina -- Foreign relations -- United States; Cuba -- Foreign relations -- United States; Cuba -- History -- Revolution, 1959.; Mexico -- History -- European intervention, 1861-1867.; Diplomatic and consular service, American -- Cuba; United States -- Foreign relations -- Argentina; United States -- Foreign relations -- Cuba; Diplomats